If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(8y+4)-17=-2(4y-8)
We move all terms to the left:
4(8y+4)-17-(-2(4y-8))=0
We multiply parentheses
32y-(-2(4y-8))+16-17=0
We calculate terms in parentheses: -(-2(4y-8)), so:We add all the numbers together, and all the variables
-2(4y-8)
We multiply parentheses
-8y+16
Back to the equation:
-(-8y+16)
32y-(-8y+16)-1=0
We get rid of parentheses
32y+8y-16-1=0
We add all the numbers together, and all the variables
40y-17=0
We move all terms containing y to the left, all other terms to the right
40y=17
y=17/40
y=17/40
| 4b+6=46 | | q(q-14)(4q-7)=0 | | 4(s+5)=32 | | (2x+8)/6+8=x+4 | | 2x+2+30+3x=0 | | x+(x+30)+2x= | | 16x-3=10x+18 | | x(x+5)=73 | | 3.4+x=18 | | 9-1/3=5/3n | | N^=5n | | 10x–15=85 | | 3(3x−1)=9x+7 | | (2x-8)=(3x-12) | | H(4)=-16(4)^2+68t+2 | | 2/3m-5=13 | | 3.8x-8.5=10.5 | | 9u+8u=2^0 | | 2.5(2z+5)=5(5(z+2.5) | | 0.1x+0.001=1/100(x+10 | | |1/2y+8|=|1/5y+2| | | 3(8x+2)=6x-10 | | |-12|-n=19 | | 18=1/2(r^2)(1/9) | | 2m+7m=10 | | (3/7)w-11=(-4/7w) | | 1/3m-6=5 | | 2*y+13=75 | | 4-7+4c=7c+6 | | 2xY+13=75 | | -3(x-2)+x=24 | | 10-5t+10=40 |